Causes of ambiguity business terms in a market economy (Eurasian Journal of Philology Science and Education, 2015)
Language reform is important for all the economic changes in the countries of the former Soviet Union. The author discusses the operation of the business terminology, which are deeply rooted in the Russian language picture of the world and the Kazakhs. The phenomenon of polysemy is the ability to have multiple word meanings generated by the action of the law of economy of speech means. The appearance of the terminological ambiguity in businessdue to the fact that the terminology of the humanities polysemy is one of the specific characteristics that largely determined by the closeness of their vocabulary of common use. Business, as one of the phenomena of social life, is also experiencing a similar effect.
Keywords: business terminology; Polysemy; ambiguity; inter-industry Polysemy.